Evaluation of Buggy Car Service Arrangement for Passengers with Special Needs: A Case Study at Sultan Hasanuddin International Airport - Fitrah, Fitrah Abdillah Azzury Munthe; Sundoro; Lestary, Dwi (Jurnal Teknologi Kedirgantaraan, 2025)
This study aims to evaluate the operational arrangement of buggy car services for passengers with special needs at Sultan Hasanuddin International Airport in Makassar. Using a qualitative descriptive approach and case study design, data were collected through field observation, interviews, and documentation during a five-month internship in the Airport Operation Landside and Terminal (AOLT) division. The findings indicate that the service implementation still faces several critical issues, such as limited vehicle availability, overcapacity usage, lack of standardized service points, misuse by non-priority passengers, and the absence of written Standard Operating Procedures (SOPs). These problems contribute to inefficiencies, safety risks, and unequal service for those entitled to priority treatment. The study recommends the formulation of structured SOPs, additional pick-up/drop-off points, regular training for AOLT personnel, and the adoption of digital support systems to enhance the effectiveness and fairness of buggy car services. By improving management policies and operational consistency, the service can better reflect the values of inclusive and human-centered airport operations, in line with Regulation of the Minister of Transportation No. 41 of 2023